2008
DOI: 10.1039/b717724k
|View full text |Cite
|
Sign up to set email alerts
|

On a chip demonstration of a functional role for odorant binding protein in the preservation of olfactory receptor activity at high odorant concentration

Abstract: The molecular mechanisms underlying odorant detection have been investigated using the chip based SPR technique by focusing on the dynamic interactions between transmembrane Olfactory Receptor OR1740, odorant ligands and soluble Odorant-Binding Protein (OBP-1F). The OR1740 present in the lipid bilayer of nanosomes derived from transformed yeasts specifically bound OBP-1F. The receptor preferential odorant ligand helional released bound OBP-1F from the OR-OBP complex, while unrelated odorants failed to do so. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 59 publications
3
60
0
Order By: Relevance
“…Some ORs, including human OR1740, were reported not to heterodimerize with a non-olfactory GPCR, the ␤ 2 -adrenergic receptor (15). Our previous studies (6,16,17), in line with others (18,19), showed a bell-shaped OR dose-response curve upon odorant stimulation. Several assumptions have been raised to elucidate the decreased OR response at high ligand concentrations (20 -22).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Some ORs, including human OR1740, were reported not to heterodimerize with a non-olfactory GPCR, the ␤ 2 -adrenergic receptor (15). Our previous studies (6,16,17), in line with others (18,19), showed a bell-shaped OR dose-response curve upon odorant stimulation. Several assumptions have been raised to elucidate the decreased OR response at high ligand concentrations (20 -22).…”
supporting
confidence: 63%
“…In insects, OBPs are thought to interact with ORs and play a scavenger role to maintain ORs in an active conformation (5). We have recently demonstrated a tripartite functional interaction between OBPs, odorants, and ORs in mammals (6).…”
mentioning
confidence: 99%
“…As already mentioned, the spectrum of OBPs in animal species can be expanded through phosphorylation and glycosylation. Further, it has been shown with the chip based surface plasmon resonance technique that the OBP is able to modulate the activity of olfactory receptors (Vidic et al, 2008). Some evidence for subtle conformational changes in rat and porcine OBPs after ligand binding has been obtained in molecular dynamics studies wherein opening of the -strand pair was observed (Hajjar et al, 2006).…”
Section: Odorant-binding Proteinsmentioning
confidence: 97%
“…Additionally, we think that systems for the solubilization of ligands into the device will help our system. Although ligands are dissolved by DMSO in this study, gas permeable materials and usages of odorant-binding proteins will be useful for incorporation of volatile chemicals into the fluidic device (32).…”
Section: Methodsmentioning
confidence: 99%